Surgical Management of Multiple Vaginal Fibroma in a Golden Retriever - Udehiya, Rahul Kumar; Mathew, Dayamon David; Kumar, Sarvan; Singh, Naresh Kumar (Biology, Engineering, Medicine and Science Reports)
A 5-year-old female golden retriever was presented with a history of swelling in perineum region with difficulty in urination and blood in urine. The case was diagnosed with vaginal fibroma on physical examination. The fibroids were removed surgically using episiotomy technique. Followed by ovariohysterectomy performed after one month. The histopathological examination of vaginal fibroma revealed the anaplastic cells show marked pleomorphism and aggregation of mononuclear cells with the bundles of spindle shaped fibrous connective cells confirmed as vaginal fibroma. The recovery was excellent and no reoccurrence was recorded up to six months follow-up
Keywords: Dog; Golden Retriever; Vagina; Fibroma; Episiotomy